Design and manufacturing of a piezoelectric traveling-wave pumping device - Hernandez, Camilo (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2013)
In this article, we present the design and construction of a micropump exhibiting a nontraditional pumping principle whose design is achievable at very low scales. The operation is based on the action of a mechanical traveling wave deforming the bottom wall of a flexible channel containing a fluid. The paper treats for the first time the influence of the traveling wave parameters on the performance of the pump with the help of finite element simulations. The results obtained from the simulation are subsequently used for the dimensioning of the linear ultrasonic traveling wave actuator that drives the device. Finally, a very simple channel-reservoirs structure was conceived to test the device. At this point, several measurements of flow rate and back pressure were carried out to estimate the performance of the prototype for different values of wave amplitude. The article finishes with a comparison between the numerical and experimental results and a brief section of discussion and conclusions